Transcription of GABAA receptor subunits in circulating monocytes and association to emotional brain function in premenstrual dysphoric disorder - Louise Stiernman; Erika Comasco; Maja Johansson; Marie Bixo (Translational Psychiatry)
Abstract Premenstrual dysphoric disorder (PMDD) has been hypothesized to be related to an altered sensitivity of the γ-aminobutyric acid type A (GABAA) receptor to progesterone-derived neurosteroids. GABAA receptor sensitivity to neurosteroid-modulation is dependent on its subunit composition. In the present study, we used quantitative reverse transcription polymerase chain reactions (RT-qPCR) to compare messenger ribonucleic acid (mRNA) expression of GABAA receptor subunits in peripheral mononuclear cells (PBMCs) across the menstrual cycle in 29 women with PMDD and 27 controls. We related mRNA subunit expression to serum levels of neurosteroids and to functional activation of the amygdala, a key brain region involved in emotion generation, measured using functional magnetic resonance imaging (fMRI). Women with PMDD had lower mRNA expression of the delta GABAA receptor subunit during the symptomatic, luteal phase (compared to the asymptomatic, follicular phase) of the menstrual cycle. Lower delta mRNA expression was related to higher amygdala activation in PMDD women. GABAA receptors incorporating the delta subunit are especially sensitive to neurosteroid modulation. It is possible that the mood symptoms of PMDD are mediated by an inability to effectively adjust the expression of this receptor type in response to neurosteroid fluctuations, leading to dysregulation GABAergic tone and increased activity in emotion-generating brain circuits.